Optimizing quality of service for sensor enabled Internet of healthcare systems - Anil Kumar Sagar (Elsevier, 2021)
Wireless Body Area Network is one of the applications of Wireless Sensor Network, for monitoring the health of the patient. Sensor nodes that are used in WBAN are of various types such as ECG sensor, BP sensor, Glucose sensor, Temperature sensor, Pressure sensor, Motion sensor, etc., depends upon the health condition of the patient prescribed by the Doctors/Physician. These nodes can create a connection to the medical server where the physician can access those data and supplied real-time services to the patient via SMS/E-mail. In WBANs, sensor nodes are either implanted inside or outside the body of the patient that senses various physiological actions in the body to get consistent and accurate data.In this paper, various aspects related to WBAN are discussed, like the quality of the sensor node, the effect of electromagnetic radiation on the human body released by the sensor node, energy consumption, and size of the sensor node that can be easily adjustable inside the human body. Energy consumption is the main issue in WBANs, as the communication unit of the sensor node takes more energy from the battery unit in transmitting the data packet from the inner body sensor to the outer body devices. For transmitting the physiological data, a routing protocol is also required to satisfy QoS (Quality of Service) parameters like energy-efficient, high packet data rate, and minimum delay. QoS parameters associated with WBAN analyze their performance by simulating on MATLAB simulation tool.